Are healthcare workers more likely than the general population to consult in primary care for an influenza‐like illness? Results from a case‐control study. Issue 5 (6th May 2020) - Peytremann, Arnaud; Senn, Nicolas; Mueller, Yolanda
Abstract: Background: Healthcare workers are at increased risk of contracting influenza. However, existing studies do not differentiate professional categories or domains of the healthcare system that are most at risk. Methods: This case‐control study compared proportions of patients with professional activity in the healthcare system between cases consulting their primary care physician for an influenza‐like illness (ILI) and controls from the general patient population of the same practices of the Swiss sentinel network. Influenza was confirmed by rRT‐PCR in a subset of practices. Analysis used a mixed logistic regression model, including age and sex as potential confounders. Results: During the 2018/2019 influenza surveillance season, out of 4287 ILI cases and 28 561 controls reported in 168 practices, 235 (5.5%), respectively 872 (3.1%), were active in the healthcare system. After adjustment, being active in health care increased the odds of consulting for an ILI (OR 1.66, 95% CI 1.40‐1.97). The association was strongest for physicians and nursing aides. In terms of work setting, odds of consulting for ILI were increased for professionals of almost all healthcare settings except home‐based care. Conclusion: Individuals active in the healthcare system were more likely to consult their primary care physician for an influenza‐like illness than for another reason, compared with individuals not active in the healthcare system. These results warrant further efforts to understand influenza transmission in the healthcare system at large.